THE SCIENTIFIC AND TECHNICAL CREATIVITY AND ITS ROLE IN THE FORMATION OF A SPECIALIST FOR THE FOOD INDUSTRY - V. M. Tiunov; A. V. Vyatkin (Современная наука и инновации, 2023)
Fruit and berry raw materials are a valuable source of nutrients and antioxidants in the diet of the population of the Sverdlovsk region.The objects of the study were gooseberry fruits represented by the following varieties: «Moonlight Night», «Beryll», «Ural grapes», «Demidovsky», «Severyanin», «II-12-4», «II-7-7,8- ser», «I-8-7», «I-7-21», «I-7-2-17-0,5». The authors found that the growing varieties of gooseberries in the Sverdlovsk horticulture breeding station could be an important source of antioxidant indicators.Gooseberry varieties have the highest values: «Moonlight Night» – 17.945 mmol/l × eq, «Ural grapes» – 14.985 mmol/ l × eq, «Severyanin» – 12.227 mmol/l × eq and «Demidovsky» - 11.957 mmol/l × eq.It was also found that the studied varieties of gooseberries have high physicochemical and biologically active substances, which indicates the possible use of this fruit and berry raw materials in the food industry, for the production of various dishes and products such as juices, purees, various types of drinks, etc.